STUDI KOMPARASI ANGKA KUMAN UDARA PADA RUANG PERAWATAN KELAS III DI IRNA II RSUD PROF. DR. MARGONO SOEKARJO PURWOKERTO TAHUN 2014 - Muhammad Fuad; Priyo Santoso; Khomsatun Khomsatun (Poltekkes Kemenkes Semarang, 2015)
The Hospital of Prof. Dr. Margono Soekarjo Purwokerto is a type B regional hospital that providesspecialist medical care and subspecialty limited. Treatment Room at IRNA II Class III is room surgicaltreatment for the disease, so that the potential occurrence of nosocomial infections. The purpose of thisstudy was to determine whether there are differences in the numbers of germs existing air in 6 types ofclass III treatment rooms of IRNA II in hospitals of Prof. Dr. Margono Soekarjo Purwokerto.This research is an analytic observational study with cross sectional approach. Type variables usedwere the independent variables (sanitary conditions in the third class ward IRNA II), the dependentvariable (number of air germs), potentially confounding variables (temperature, humidity, lighting,ventilation and a wide density residential).Based on the results of the examination, the average - average rate of 6 indoor air bacteriaexamined was 157.5 CFU/m3. Average - The average temperature is 29,630 C. Average - averagehumidity is 69.05%. Average - average is 122.5 Lux lighting. Ventilation holes wide average - average is13.5 m2. Average occupancy density - average is 17.55 m3.Researchers concluded in the third class ward IRNA II is not fully qualified fully seen from thequality of the physical environment. Researchers suggest a number of bacteria should be monitored asan indicator of air disinfection room does.